Extracting the Workforce Learning Curve for Selected Iranian Manufacturing Industries - Samadi Varankesh , Somayeh; Asadi, Ali Asghar; Saedi, Omid (Management Analytics and Social Insights, 2024)
In industrial economics, the learning curve illustrates that production costs decrease continuously as the number of production units increases due to an improvement in the learning rate as production increases. The objective of this research is to explore the concept of the workforce learning curve in the Iranian manufacturing industry from 1996 to 2015. The study uses panel data econometric methods, specifically the Fixed Effects method, to extract the learning curve model for six industrial activities within Iran's economy to achieve this. According to the econometric model results, it has been confirmed that the learning curve for the selected industries follows a quadratic model that is inverted U-shaped. Therefore, focusing on increasing production and utilizing economies of scale in these sub-sectors is advisable.